CT angiography to evaluate coronary artery disease and revascularization requirement before trans-catheter aortic valve replacement - Rossi, Alexia; De Cecco, Carlo N.; Kennon, Simon R. O.; Zou, Lu; Meinel, Felix G.; Toscano, William; Segreto, Sabrina; Achenbach, Stephan; Hausleiter, Joerg; Schoepf, U. Joseph; Pugliese, Francesca (Journal of Cardiovascular Computed Tomography, 2017)
BACKGROUND: Coronary artery disease (CAD) and aortic stenosis share pathophysiological mechanisms and risk factors. We evaluated the clinical utility of coronary computed tomography angiography (CTA) to identify CAD and revascularization requirement in patients with severe aortic stenosis considered for transcatheter aortic valve replacement (TAVR). METHODS: Consecutive patients without known CAD underwent calcium scoring, CTA and invasive coronary angiography (ICA). A second-generation dual-source CT scanner was used. ICA-quantitative coronary angiography (QCA) served as reference standard. CAD was reported using a lenient threshold of ≥50% and a stricter threshold of ≥70% diameter reduction. Findings of ≥70% diameter reduction and of high-risk CAD were used to predict revascularization. RESULTS: The study included 140 patients [68 males; 82.3 (7.7) years]. CAD defined by the 50% threshold on ICA was found in 58/140 (41%) patients. CAD by the 70% threshold was found in 23/140 (16%) patients. High-risk CAD was found in 16/140 (11%) patients. CTA and ICA had similar odd-ratios of 3.22 (1.26-8.23) and 4.62 (1.64-13.05), respectively, in predicting revascularization. Forty-two/140 (30%) patients had <400 Agatston calcium score, 98/140 (70%) patients had ≥400 calcium score. The diagnostic performance of CTA in the low calcium score group was better than the high calcium score group (AUC 0.81 vs. 0.63). CONCLUSION: CTA remained questionable to rule-out CAD as gatekeeper to ICA in TAVR candidates who had severe coronary calcifications. In patients with less severe coronary calcifications, accounting for 30% of participants in this study, CTA may play a clinical role.
EVALuna2:33618